Determination of the Flight Range and Dispersal of the House Fly, Musca domestica (L.) using Mark Release Recapture Technique - Nazni, W.A.; Luke, H.; Rozita, W.M.W.; Abdullah, A.G.; Sa'diyah, I.; Azahari, A.H.; Zamree, I.; Tan, S.B.; Lee, H.L.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2005)
In order to control any pest it is essential to study the life cycle, biology and bionomics of the target pest under control. With this respect, we have studied the flight range of the house fly Musca domestica (L.). The flight range of the house fly from two sites i.e, the poultry farm and a stable farm has been studied. The flight range study was conducted using a mark release technique. The approach we used in this study was that the flies collected from the respective farms were marked and released at different distances from the farms. The flies were then re-captured from the poultry farm and the stable farm. Studies conducted elsewhere use the technique of releasing the insect species at one spot and recapturing the insect species with the help of baited traps placed at various locations from the release point. The advantage of the approach used in this study was that the flight range as well as the homing effect was determined. From this study, the flight range of house flies released at the poultry farm was 7 km whereas flight range for flies release from stable farm was 5 km. The recovery rate of house flies at the poultry and stable farm was 0.05 and 0.016, In this study, marked specimens has been detected up to 8 days in field conditions indicating that under field condition the life expectancy could be in the range of 1-2 weeks.